Cerebellar Tremor Caused by Meningoencephalitis Tuberculosis in A 17-Year-Old Patient: A Case Report - Johansen, Johansen (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2025)
Meningitis Tuberculosis (TB) is a rare manifestation of extrapulmonary TB and can progress to Meningoencephalitis. Cerebellar tremor is a tremor in the head caused by cerebellar diseases such as strokes, tumors, multiple sclerosis, and certain drugs. This study describes a case of a 17-year-old boy who was infected with TB meningoencephalitis with cerebellar tremors. A 17-year-old boy came to the emergency room at K.R.M.T. Wongsonegoro Hospital with the main complaint of shaking head. The patient was diagnosed with meningoencephalitis TB and cerebellar tremors. Meningitis TB occurs due to the hematogenous spread of primary pulmonary TB or from rupture of the subependymal tubercles into the subarachnoid space and can progress to Meningoencephalitis. Clinical manifestations that can appear are a combination of meningitis and encephalitis and movement disorders caused by encephalitis. The management obtained in this patient was TB drugs, corticosteroids, and anti-seizures. Cerebellar tremor is one of the clinical manifestations caused by Tuberculosis encephalitis that must be watched out for to get adequate treatment.